2000
DOI: 10.1074/jbc.m001271200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating Mutation of the Mouse Tissue Inhibitor of Metalloproteinases-2(Timp-2) Gene Alters ProMMP-2 Activation

Abstract: To understand the biologic function of TIMP-2, a member of the tissue inhibitors of metalloproteinases family, an inactivating mutation was introduced in the mouse Timp-2 gene by homologous recombination. Outbred homozygous mutants developed and procreated indistinguishably from wild type littermates, suggesting that fertility, development, and growth are not critically dependent on TIMP-2. Lack of functional TIMP-2, however, dramatically altered the activation of proMMP-2 both in vivo and in vitro. Fully func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 26 publications
(28 reference statements)
9
109
0
4
Order By: Relevance
“…Special membrane type MMPs (MT-MMP) cleave this complex into the active form of MMP. 33 This immunohistochemical study showed the expression of TIMP-2 to be slightly increased in tumour cells compared to nonmalignant tissue. This finding supports the relevance of TIMP-2 in the activation of the MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Special membrane type MMPs (MT-MMP) cleave this complex into the active form of MMP. 33 This immunohistochemical study showed the expression of TIMP-2 to be slightly increased in tumour cells compared to nonmalignant tissue. This finding supports the relevance of TIMP-2 in the activation of the MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, other study showed that TIMP-2 binds to active MT1-MMP but not to latent MT1-MMP (Hernandez-Barrantes et al, 2000). Fully functional TIMP-2 is essential for e cient activation of proMMP-2 both in vitro and in vivo (Caterina et al, 2000). However, the active 65-kDa MMP-2 can be inhibited by plasma membrane-bound TIMP-2 (Itoh et al, 1998).…”
Section: Paradox 2: Timps Regulate Pro-mmp Activation and Tumor Angiomentioning
confidence: 95%
“…Despite the importance of TIMP-2 and integrin ␣v␤3 in the autoproteolytic activation of MMP-2 following MT1-MMPcleavage (10,33,47), these molecules are not likely to be involved in the complete activation of factor Xa-processed MMP-2. Full activation of MMP-2 was not affected in MCF-7 cells that express negligible amounts of TIMP-2 and HEK293F cells transfected with integrin ␣v small interfering RNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, trypsin-2-processed MMP-2 was obtained by incubating purified pro-MMP-2 with trypsin-2 under cell-free conditions (40). Therefore, autoproteolytic processing of trypsin-2-cleaved MMP-2 is not likely to occur, since cellular molecules, such as TIMP-2 and integrin ␣v␤3, may be required for the maturation of partially processed MMP-2 to its fully active form (10,12,33,47). This may explain the partial activation of trypsin-2-processed MMP-2 seen under cell-free conditions.…”
Section: Discussionmentioning
confidence: 99%